Influence of technological parameters on the air heater exergy efficiency of the heat recovery system boiler plant - Fialko, N.; Stepanova, A.; Navrodska, R.; Meranova, N.; Shevchuk, S. (Energy and Automation, 2024)
The analysis results of the technological parameters influence on the air heater exergetic efficiency of the heat recovery system a boiler plant with a heating capacity of 2 MW are presented. A comprehensive methodology based on the balance methods of exergetic analysis and the selection of the necessary evaluation criteria was used to evaluate the efficiency. Exergetic losses and heat-exergetic efficiency criterion, which characterizes exergetic losses per unit of heat output of the air heater, were chosen as these criteria. Using the developed methodology, the nature and regularities of the heating capacity the plate air heater influence on its exergetic efficiency were established. The local exergetic losses associated with heat transfer between heat-transfer agents, wall thermal conductivity, and heat-transfer agents motion, as well as their relative contribution to the total local exergetic losses, are investigated. It was established that the largest exergetic losses and the heat- exergetic efficiency criterion in the air heater for all values of its heat output are related with heat transfer from the wall to the air. The values of exergetic losses and the heat-exergy efficiency criterion for heat transfer from flue gases to the wall are 1.4-1.5 times less than the exergetic losses for heat transfer from the wall to the air. The values of exergetic losses and the heat-exergy efficiency criterion related with wall thermal conductivity and heat-transfer agents movement are, on average, an order of magnitude lower. It was established that to increase the air heater exergetic efficiency, it is advisable to reduce local exergetic losses by increasing the heat transfer coefficients, mainly by increasing the heat transfer coefficient from the wall to the air. The optimal values heating capacity of the air heater studied, which corresponds to its high exergetic efficiency, does not exceed 55 kW. Key words: exergy analysis methods, air heater of boiler plant, exergy efficiency